2014/15 Picking, Roadsiding, and Hauling Charges for Florida Citrus - Ariel Singerman (EDIS)
As Florida’s citrus industry confronts the impacts of Huanglongbing (HLB or citrus greening)–decreasing crop yields and production, lower quality fruit, and increasing cost of production–many growers are facing declining returns. A 2015 survey of twelve Florida citrus harvesters to collect data on harvesting charges during the 2014/15 season revealed that average picking and roadsiding charges for fresh fruit are in most cases lower than those for processed fruit, likely because of the impact of HLB. This 3-page fact sheet presents the results of the survey and provides a table summarizing the harvesting charges for citrus during the 2014/15 season with the average and the range of picking and roadsiding charges by variety and type of fruit (fresh versus processed), as well as the average hauling charges for all varieties by distance. The fact sheet will assist growers in the effort to compute the changes to their economic returns as the industry adapts to remain profitable. Written by Ariel Singerman of UF/IFAS Citrus Research and Education Center, and published by the Food and Resource Economics Department, November 2015.